2019
DOI: 10.4236/ajcc.2019.81008
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Future Rainfall over the Mono River Basin of West-Africa

Abstract: This study assessed the rainfall trends and changes over Mono river basin under the highest greenhouse gas emission scenario RCP8.5. Simulations of eight regional climate models (RCMs) provided by Africa-CORDEX program were considered. To analyze the performance of a set of regional climate models, the MBE (mean bias error), the RMSE (root mean square error), the volume bias (VB), correlation coefficient (R 2) and the t-Test statistics were calculated. The precipitation concentration index (PCI), Mann-Kendall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Rainfall volatility analysis is based on calculating the coefficient of variation (CV), the standardized precipitation anomaly index (SPAI), and the precipitation concentration index (PCI) [17], while the trend is analyzed by using Mann-Kendall (MK) test [2,[18][19][20][21]. SPAI was used to display quantitative analysis related to changes in rainfall and identify potential floods or droughts [8,22], where rainfall is seasonal and periodic in a monsoon-dominated climate context [23], like the climate in Indonesia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rainfall volatility analysis is based on calculating the coefficient of variation (CV), the standardized precipitation anomaly index (SPAI), and the precipitation concentration index (PCI) [17], while the trend is analyzed by using Mann-Kendall (MK) test [2,[18][19][20][21]. SPAI was used to display quantitative analysis related to changes in rainfall and identify potential floods or droughts [8,22], where rainfall is seasonal and periodic in a monsoon-dominated climate context [23], like the climate in Indonesia.…”
Section: Methodsmentioning
confidence: 99%
“…Table 4 present the annual PCI values based on monthly rainfall data each year. The classification criteria using the criteria introduced by Oliver in 1980 [21] are presented in Table.5. The average PCI in the 2007-2018 periods was 19.67, which was classified as a high concentration of rainfall.…”
Section:  =mentioning
confidence: 99%
“…The analysis of the maximum duration of wet sequences shows a sharp decline in the Mono basin (Batablinlè et al, 2018). Ly et al (2013) showed a gradual decrease in the maximum duration of the number of wet sequences in West Africa since 1960. Our work shows that such an evolution diagnosed on the present climate is likely to persist in the future.…”
Section: Discussionmentioning
confidence: 99%
“…This study area has already been described by certain authors (Batablinlè et al, 2018;Lamboni et al, 2019b).…”
Section: Study Areamentioning
confidence: 95%
“…The lowest rainfall is about 300 mm/year recorded in Sahel area and the highest value is obtained at mountainous area with total precipitation amount about 2400 mm/year. The climate system over Mono and Bandama river basin are presented by Lamboni et al [16] and Soro et al [17], respectively. The northern part presents unimodal rainfall regime while the central and southern part show bimodal.…”
Section: Study Areamentioning
confidence: 99%